Electrolyzed water as a sustainable cleaning and disinfection chemical for SMEs Malaysian meat processing food industries: challenges and uncertainties - Khalid, Nurul Izzah; Ab Aziz, Norashikin; Mohd Thani, Nurfatimah; Shapi’i, Ruzanna; Abd Rahman, Nur Farhana (SixScientia Resources, 2020)
The cleaning and disinfection are also known as sanitation process and it is a prerequisite for most of food safety standards. Sanitation process is often neglected by industrialist due to it is a plant downtime and incurs cost. Limited resources and knowledge have prevented the implementation of effective cleaning and sanitation process in the Small and Medium-sized Enterprises (SMEs) food factories in Malaysia. The commercial food-grade chemical which is expensive can be a burden for SMEs food manufacturers. Hence some of the SMEs food manufacturers have opted for non-food grade cleaning chemicals (e.g., laundry detergent) to clean their food processing equipment and factory environment. The non-food grade chemical is less rinsible and can leave a fragrance. The application of this non-food grade chemical not only caused chemical contamination to food products but also on riverine. The improper disposal of wastewater sourcing from the Malaysian food industry is known to pose pollution problems and violate environmental regulation. The odourless and rinsible electrolyzed water (EW) is seen as a potential alternative for the commercial cleaning and sanitation detergents. Moreover, papers are claiming that there is no wastewater treatment are needed when the EW is used as the cleaning and disinfecting chemicals.